Erratum: Off-resonant dielectronic recombination in a collision of an electron with a heavy hydrogenlike ion: (Phys. Rev. A 81, 062703 (2010)) - Yerokhin, Vladimir; Surzhykov, Andrey (Physical review. A, Atomic, molecular, and optical physics, 2011)
DOI:https://doi.org/10.1103/PhysRevA.83.059908